VALIDITY TEST CONSTRUCTION MEASURESEPG (TEACHER PROFESSIONAL ETHICS) "PERSONAL VALUE DIMENSION" - Eva Dwi Kumala Sari; Burhanuddin Tola; Gaguk Margono (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2019)
The purpose of this study was to examine the construct validity of teacher professional ethics measures modified from the Yael Fisher scale (Yael Fisher, 2013) and adapted to the culture in Indonesia, the Indonesian version made by researchers. Teacher professional ethics consists of three dimensions namely, personal value, social value and universal value. In this article, the discussion is only in the dimension of personal value. Researchers used data from 178 state elementary school teachers in the Jakarta area. The analytical method used in this study is first order Confirmatory Factor Analysis (CFA) with the help of M-Plus. The results of the analysis in this study indicate that in general the items in the Professional Ethics of the Teacher's personal value dimension have measured unidimensional constructs. The factor load coefficient for the item measurement of personal value is at the value t> 1.96, meaning that the item is significant. The results also show the factor model that is fit with Chi-square = 264.161 *, df = 157, P-value = 0.0010, RMSEA = 0.062, CFI = 0.977 and using the MLR estimator the H0 scaling correction factor is 1.0259 (close to 1 ) states that this model is fit with the data. Keywords: Teacher Professional Ethics, personal value, validity, CFA